PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN PENGETAHUAN HURUF ABJAD PADA PESERTA DIDIK KELAS 1 DI SD NEGERI 15 FAFANLAP - Siti Dahlia Rahanyamtel; Alif Hasanah; Muhammad Ramli (CV. ADIBA ASIHA AMIRA, 2026)
The study was conducted with the aim of explaining the use of local wisdom-based audio-visual media in improving the knowledge of alphabet letters in grade one students at Public Element School 15 Fafanlap, Raja Ampat Regency. The type of research used in this study is experimental research with a quantitative approach. The design in this study is a pre-experimental design with one-group Pretest-Postest. This design was used because this study only involved one class, namely the experimental class, which was carried out by comparing the results of the pretest with the results of the posttest design. The results of the study used in Public Element School 15 Fafanlap, Raja Ampat Regency with a sample of grade 1 students consisting of 30 students. In this study, the researcher provided treatment in the form of before and after the use of audio-visual media based on local wisdom to improve knowledge of the alphabet by using pretest and posttest in class 1 at Public Element School 15 Fafanlap, Raja Ampat Regency. Based on the results and discussion above, it can be concluded that there is a significant influence between audio-visual media activities on knowledge of the alphabet based on local wisdom in class 1 students at Public Element School Fafantap, Raja Ampat Regency. This can be proven in the analysis of the results of the posttest score which is higher than the pretest score of the students.